Study on Zonal Cooperative Control Technology of Surrounding Rock of Super Large Section Soft Rock Chamber Group Connected by Deep Vertical Shaft - Shengrong Xie; Zaisheng Jiang; Dongdong Chen; En Wang (Advances in Civil Engineering)
Aiming at solving the problem of asymmetric deformation, failure, and stability control of surrounding rock caused by the excavation of deep super large section soft rock chamber group passing through multilayer strata, taking super large section soft rock chamber group connected by deep vertical shaft in Wuyang Coal Mine as the engineering background, the deformation development mode of surrounding rock, the expansion situation of loosening range, and the plastic failure response characteristics in chamber group under the disturbance influence are monitored and numerically analyzed. On this basis, the super large section chamber group is divided into four maintenance control areas: area I (severe deformation area), area II (stable deformation area), area III (medium deformation area), and area IV (small deformation area), and the asymmetric deformation and failure mechanism of the surrounding rock of the chamber group is analyzed. The influence mechanism of specific support technologies on the deformation control effect of surrounding rock of chamber group is systematically studied, including high-strength prestressed bolt (cable) mesh shotcreting coupling support technology, reinforced concrete wall subarea brickwork support technology, and hollow bolt (cable) grouting reinforcement technology of fragmented coal and rock mass. The basic control ideas and technical methods of surrounding rock of deep large section soft rock chamber group are formed. The subarea collaborative control technology of “high-strength prestressed bolt (cable) mesh shotcreting coupling + reinforced concrete wall brickwork support technology + high-strength bolt (cable) grouting of fragmented coal and rock mass” is proposed. The field application shows that this technology realizes effective control of surrounding rock of super large section chamber group.